HUBUNGAN INDEKS MASSA TUBUH DAN LINGKAR PINGGANG DENGAN KEJADIAN HIPERTENSI PADA ORANG DEWASA USIA PRODUKTIF DI POSBINDU DESA KADUGADUNG - Ajrur Rahman; Frisca (Fakultas Kedokteran Universitas Tarumanagara, 2025)
High blood pressure is part of the group of non-communicable diseases and is often referred to as “The Silent Killer” because it usually does not show symptoms but can lead to serious complications. According to estimates from the World Health Organization (WHO), the number of adults with hypertension worldwide reaches approximately 1.28 billion, with the majority of cases identified in developing countries. In Indonesia, the prevalence of hypertension reaches 34.11% and is more commonly found in women. One of the main contributing risk factors is obesity, including both general and central obesity. Obesity occurs when there is an imbalance between calorie intake and the amount of energy expended by the body, thereby affecting increased blood volume and causing vascular resistance. Assessment of obesity is generally carried out using the Body Mass Index (BMI) parameter as well as waist circumference measurement. The objective of this study was to examine the relationship between BMI and waist circumference with the occurrence of hypertension in the productive-age population at Posbindu, Kadugadung Village. Analysis of 154 respondents revealed a significant association between BMI and the incidence of hypertension (p = 0.035; PRR = 1.516; OR = 2.032; CI did not cross 1). These results indicate that individuals with obesity have a 1.516-fold higher risk and a 2.032-fold greater likelihood of developing hypertension compared to non-obese individuals. In contrast, waist circumference did not show a significant association with hypertension (p = 0.341; PRR = 1.208; OR = 1.372; CI includes 1).